The Efforts in Improving the Civics Learning Achievement through Cooperative Learning Method of STAD Model (Student Teams Achievement Division) on the Grade VI Students of Semester 2 at SDN Karangsemanding 02 Jember in 2017/2018 Academic Year - Setyagung Budi Cahyono (Pancaran Pendidikan, 2020)
Collaborative learning activities are able to trigger the active learning. Teaching and learning activities done in the classroom stimulate the active learning. Hence, doing the exercises or tasks within small groups and explaining the ideas to others are used to foster the students' activities. Based on the results of this research, the conclusions drawn were: (1) The cooperative learning method of STAD model improved the quality of Civics learning. (2) The cooperative learning method of STAD model gave a positive impact in improving the students’ learning achievements indicated by an increase in the student’s learning completeness on each cycle, involving cycle I (68.96%), cycle II (86.20%), cycle III (100). %). (3) The cooperative learning method of STAD model provided the students with the attention and opportunity to deliver their opinions, thoughts, ideas, and questions. (4) The students were able to work independently or within group, and be responsible on the individual and group assignments.